2007
DOI: 10.1097/mph.0b013e3180437e02
|View full text |Cite
|
Sign up to set email alerts
|

Thalassemia in Iran

Abstract: Owing to the national prevention program and provided special care, the age distribution of thalassemic patients in Iran is getting adapted to a full prevention and treatment program and life expectancy of these patients has been increased considerably. This shift in the age distribution of thalassemia, a traditionally considered pediatric disease, will face us with new challenges and the health care system should be prepared for this new face of thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 13 publications
2
67
1
Order By: Relevance
“…It has also reported that over 70% of thalassaemia patients in Iran are older than 10 years [29]. In Iran, the prevalence of anti-HCV in hemophiliac is from 15.65% to 76.7% in patients from various geographical regions [30]. The majority of positive cases among hemophiliacs refl ect treatment with unscreened or not effi ciently inactivated blood products in the past.…”
Section: Discussionmentioning
confidence: 99%
“…It has also reported that over 70% of thalassaemia patients in Iran are older than 10 years [29]. In Iran, the prevalence of anti-HCV in hemophiliac is from 15.65% to 76.7% in patients from various geographical regions [30]. The majority of positive cases among hemophiliacs refl ect treatment with unscreened or not effi ciently inactivated blood products in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is located on the "Thalassemia Belt" in the Eastern Mediterranean region of World Health Organization (WHO). Iran is indeed one of most important countries with high prevalence of β-thalassemia major (Ghotbi & Tsukatani, 2005;Rezaee et al, 2012;Abolghasemi et al, 2007). Although the exact prevalence rates of β-thalassemia major in Iran are not available; however, it is estimated that prevalence rate of β-thalassemia major carriers in Iran is about 4% which is significantly higher than the average β-thalassemia major gene prevalence (1.5%) of world (Miri et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Based on different studies, the prevalence of HCV infection in patients with thalassemia is approximately 4.4% -85% in the world (11,12). The incidence of HCV infection in children with β-thalassemia major in Egypt is reported 40% (13). In another study in Pakistan, the prevalence of HBV and HCV infections in patients with thalassemia was reported 1.7% and 35%, respectively (14).…”
Section: Introductionmentioning
confidence: 99%